Tai Chi as a complementary exercise for pulmonary rehabilitation in chronic obstructive pulmonary disease: A randomised controlled trial - Wei Liu; Xue-Mei Liu; Ya-Ling Huang; Peng-Ming Yu; Xia-Wei Zhang; Chen Zhao; Bing Mao; Jie Min; Hong-Li Jiang (Elsevier, 2023)
Objectives: With the characteristics of mindfulness and breathing techniques, Tai Chi has been recommended with therapeutic values in chronic obstructive pulmonary disease (COPD). However, its strengths as a complementary exercise for conventional pulmonary rehabilitation (PR) remain unclear. Design and setting: This single-blinded randomised controlled trial recruited patients with mild to severe stable COPD. Eligible participants were randomly assigned to the group with usual care (control), total body recumbent stepper (TBRS) exercise, Tai Chi (TC), or combined TBRS exercise and Tai Chi (TBRS-TC). Patients received a two-month hospital-based supervised exercise, followed by a ten-month community- or home-based rehabilitation program. Results: A total of 120 participants were recruited, and 102 were included in the per-protocol analysis. The mean changes in St George's Respiratory Questionnaire (SGRQ) total score from baseline to the post-hospital exercise in the control group, TBRS group, TC group, and TBRS-TC group was 2.62 (95 % CI −8.99 to 8.99), −9.28 (95 % CI −13.96 to −4.60), −10.19 (95 % CI −13.72 to −6.67), and −16.75 (95 % CI −20.25 to −13.24), respectively, with a statistically significant difference between groups in favor of the TBRS-TC exercise (P < 0.001). The remarkable effect of TBRS-TC exercise in improving the quality of life maintained until the end of the community- or home-based rehabilitation training (P < 0.001). Besides, a statistically better effect with the TBRS-TC exercise was also observed in the outcomes regarding exercise capacity, pulmonary function, symptom burden, and systemic inflammation after the whole process of 12-month integrative PR exercise programme. Conclusions: Based on the results, a novel integrated exercise modality combining Tai Chi and conventional pulmonary rehabilitation was developed. It might contribute to more positive effects in patients with stable COPD. Registration: The study was registered with the Chinese Clinical Trial Registry (ChiCTR-IOR-15006874) prior to commencing recruitment.